2009
DOI: 10.1590/s1413-78522009000500005
|View full text |Cite
|
Sign up to set email alerts
|

Estudo histopatológico do trajeto de biópsia de tumores musculoesqueléticos malignos

Abstract: Objective: To investigate whether there is any risk of seeding by neoplasic cells along biopsy tracks and to study local histological abnormalities. Methods: This was a prospective study on biopsy tracks in patients who underwent operations due to malignant musculoskeletal tumors between April 2006 and April 2007. Results: Neoplasic cell implantation occurred in 32% of the tracks.The most common histological abnormalities in positive cases were classified as severe fibrosis, mild inflammatory component and sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 9 publications
0
28
0
Order By: Relevance
“…Another empirically widespread issue is that the percutaneous biopsy technique, by involving less manipulation of the tumor tissue, also implies a lower contamination of the biopsy tract 4 7 , 16 - 18 It has also been observed that the contamination of the biopsy path is more frequent in soft tissue sarcomas than in cartilaginous and osseous lesions 13 . it is also believed that neoadjuvant chemotherapy has a protective effect in the control of tumor infiltration in the biopsy site, 17 , 19 and that this contamination has a negative value in the prognosis of affected patients 20 …”
Section: Introductionmentioning
confidence: 99%
“…Another empirically widespread issue is that the percutaneous biopsy technique, by involving less manipulation of the tumor tissue, also implies a lower contamination of the biopsy tract 4 7 , 16 - 18 It has also been observed that the contamination of the biopsy path is more frequent in soft tissue sarcomas than in cartilaginous and osseous lesions 13 . it is also believed that neoadjuvant chemotherapy has a protective effect in the control of tumor infiltration in the biopsy site, 17 , 19 and that this contamination has a negative value in the prognosis of affected patients 20 …”
Section: Introductionmentioning
confidence: 99%
“…Ribeiro et al (17) , who studied both bone and soft-tissue tumors, found four cases of contamination (57.1%) among seven cases of soft-tissue tumors and four cases of contamination (22.2%) among 18 cases of bone tumors. These authors suggested that greater cellularity and lower quantities of matrix, which are particular characteristics of soft-tissue sarcomas, would be related to greater cell dissemination, in comparison with bone tumors.…”
Section: Discussionmentioning
confidence: 97%
“…Another issue raised in the literature is the influence of the type of tumor on occurrences of tumor contamination in the biopsy path (17,29) . Ribeiro et al (17) , who studied both bone and soft-tissue tumors, found four cases of contamination (57.1%) among seven cases of soft-tissue tumors and four cases of contamination (22.2%) among 18 cases of bone tumors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations